Selection and Design Calculation of Chain for Silent Chain Conveyor - Lu Xudong; Wu Dao; Cong Fe; Wang Hongjun; Sheng Hua (Jixie chuandong)
The transmission principle for the horizontal drive conveyors of automobile factory,a selection method of chain of silent chain conveyor. A 25.4mm pitch silent chain conveyor applications is introduced. The chain design calculation step is expounded in detail. The chain selection is connected with the coefficient of friction of the support rail with the shaft spacing and other factors,a convenient method of design calculation for designers select chain is provided.